Geokimia Endapan Nikel Laterit di Tambang Utara, Kecamatan Pomalaa, Kabupaten Kolaka, Provinsi Sulawesi Tengara - Indra Kusuma, Riko Ardiansyah; Kamaruddin, Hashari; Rosana, Mega Fatimah; Tintin Yuningsih, Euis (Pusat Survei Geologi, 2019)
Pomalaa is administratively located in Kolaka Regency, Southeast Sulawesi Province. The nickel mining business area in Pomalaa is managed by State-Owned Enterprises and Private Enterprises. Pomalaa is a sub-district that has natural resources in the form of nickel. Nickel Laterite deposits is a result weathering of ultramafic rock that is leaching process and accumulates in the supergen enrichment zone. The lateritization factor is controlled by lithology, morphology, and structure. In general, the profile of laterite nickel deposits in the North Mine area from top to bottom consists of top soil, limonite, saprolite, and bedrock zones. The laterite nickel precipitate in the North Mine shows varying thickness, based on color, texture, size and mineral composition. Laterite deposits from drilling results reaches an range of 25 - 30 meters. Soil and rocks sampling from each laterite zone every meter resulting from drilling are carried out by laboratory testing using XRF (X-Ray Fluorescence) analysis method with 283 total sample. High Ni element show enrichment in the saprolite zone, whereas in the high Fe (iron) element in the limonite zone.Keywords: nickel, laterite, geochemical, Pomalaa